Biological evaluation and energetic analyses of novel GSK‐3β inhibitors. Issue 4 (26th December 2017) - Zhang, Denan; Liu, Lei; Pang, Lin; Jin, Qing; Ke, Kehui; Hu, Ming; Yang, Jingbo; Ma, Weifang; Xie, Hongbo; Chen, Xiujie
Abstract: Glycogen synthase kinase‐3 beta (GSK‐3 β ) is involved in multiple signaling pathways. Consistent with its critical roles in normal cells, abnormalities in GSK‐3 β activity have been implicated in diabetes, heart disease, Parkinson disease, and Alzheimer's disease. In this study, a series of new scaffolds of small molecule inhibitors of GSK‐3 β were identified by virtual screening and bioassay. Candidates that adhere to drug‐like criteria from a virtual library of compounds were tested using computational docking studies. Twenty selected compounds were tested, which led to the discovery of two hits. Compound 14 (IC50  = 8.48 µM) and compound 19 (IC50  = 2.19 µM) were identified with high affinity. Molecular dynamics (MD) simulations, in conjunction with molecular mechanics/Poisson‐Boltzmann surface area binding free‐energy analysis, were employed to gain insight into the binding modes and energetics of GSK‐3 β inhibitors. The detailed analysis of molecular dynamics results shows that Ile62, Val70, Tyr134, and Leu188 in GSK‐3 β are key residues responsible to the binding of compound 14 and compound 19 . Importantly, our results also validated this combined virtual screening and biophysical technique approach to discovery kinase inhibitors, which may be applied for future inhibitor discovery work for GSK‐3 β . Abstract : We have discovered potent GSK‐3β inhibitors by the virtual screening approach and biological validation. Furthermore, we performed molecular dynamics simulations to study the binding mechanism between different GSK‐3β inhibitors.